Fluoride-ion secondary battery
Patent Information
- Application Number
- JP2021033759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-03
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-03-03
AI Technical Summary
Existing fluoride ion secondary batteries require improvements in discharge capacity and energy density.
A fluoride ion secondary battery design incorporating a positive electrode layer with copper and fluorine compounds, a solid electrolyte layer containing BaCaF4 and SrCaF4, and a negative electrode layer with lanthanide fluorides doped with alkaline earth metal fluorides and carbon materials, enhancing ionic and electronic conductivity.
The battery achieves improved discharge capacity and energy density through optimized electrode and electrolyte compositions, specifically with lanthanide fluoride and carbon material combinations.
Smart Images

Figure 00000013_0000
Abstract
Description
Technical Field
[0001] The present invention relates to a fluoride ion secondary battery.
Background Art
[0002] Conventionally, lithium ion secondary batteries have been widely used as secondary batteries with high energy density. In a lithium ion secondary battery, a separator is disposed between a positive electrode and a negative electrode, and an electrolytic solution is filled therein.
[0003] Since the electrolytic solution of a lithium ion secondary battery usually contains a flammable organic solvent, there has been a problem with thermal safety in some cases.
[0004] Therefore, fluoride ion secondary batteries have been studied as all-solid-state batteries in which a solid electrolyte layer is disposed between a positive electrode layer and a negative electrode layer.
[0005] It is known to use a composite fluoride of a metal and a fluorine compound as a positive electrode active material of a fluoride ion secondary battery (see, for example, Patent Document 1).
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0007] However, it is desired to further improve the discharge capacity and energy density of fluoride ion secondary batteries.
[0008] An object of the present invention is to provide a fluoride ion secondary battery excellent in discharge capacity and energy density.
Means for Solving the Problems
[0009] One aspect of the present invention is a fluoride ion secondary battery having a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. The positive electrode layer contains a positive electrode active material, and the positive electrode active material contains a composite fluoride of copper and a fluorine compound. The solid electrolyte layer contains BaCaF4. The negative electrode layer contains a negative electrode active material, a conductive assistant, and a solid electrolyte. The negative electrode active material contains a lanthanum fluoride doped with an alkaline earth metal fluoride. The conductive assistant contains a carbon material. The solid electrolyte contained in the negative electrode layer contains at least one of BaCaF4 and SrCaF4. The lanthanum fluoride doped with the alkaline earth metal fluoride and the carbon material are composite.
[0010] The lanthanum fluoride may be one or more compounds selected from the group consisting of LaF3, CeF3, SmF3, and NdF3.
[0011] The alkaline earth metal fluoride may be one or more compounds selected from the group consisting of CaF2, SrF2, and BaF2.
[0012] The lanthanum fluoride doped with the alkaline earth metal fluoride is La 0.9 Ba 0.1 F 2.9 、Ce 0.95 Ba 0.05 F 2.95 、Ce 0.95}Sr 0.05 F 2.95 およびCe 0.95 [[ID=з5]]Ca 0.05 F 2.95}and may be one or more compounds selected from the group consisting of.
[0013] The solid electrolyte contained in the negative electrode layer may contain at least one of BaCaF4 and SrCaF4 nanoparticles.
[0014] ]END]] The solid electrolyte layer may contain BaCaF4 nanoparticles.
Advantages of the Invention
[0015] According to the present invention, it is possible to provide a fluoride ion secondary battery that is excellent in discharge capacity and energy density. [Brief explanation of the drawing]
[0016] [Figure 1] This figure shows the initial charge-discharge curves of the all-solid-state fluoride-ion secondary batteries of Example 1 and Comparative Example 1. [Modes for carrying out the invention]
[0017] Embodiments of the present invention will be described below.
[0018] <Fluoride ion secondary battery>
[0019] The fluoride ion secondary battery of this embodiment has a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, and for example, a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector are arranged in sequence.
[0020] [Negative electrode layer] The negative electrode layer comprises a negative electrode active material, a conductive additive, and a solid electrolyte. Here, the negative electrode active material comprises a lanthanide fluoride doped with an alkaline earth metal fluoride, the conductive additive comprises a carbon material, and the solid electrolyte comprises at least one of BaCaF4 and SrCaF4. Furthermore, the lanthanide fluoride doped with an alkaline earth metal fluoride and the carbon material are composited. That is, the negative electrode layer comprises a composite of a lanthanide fluoride doped with an alkaline earth metal fluoride and a carbon material (hereinafter also referred to as a composite of a lanthanide fluoride and a carbon material).
[0021] The negative electrode layer contains lanthanide fluoride doped with alkaline earth metal fluoride, thus improving ionic conductivity. Furthermore, the negative electrode layer contains a composite of lanthanide fluoride and carbon material, thus improving electronic conductivity. Additionally, the negative electrode layer contains at least one of BaCaF4 and SrCaF4, resulting in a low defluorination potential. Therefore, the discharge capacity of the fluoride ion secondary battery in this embodiment is improved.
[0022] (Negative electrode active material) The lanthanide fluoride is not particularly limited, but examples include LaF3, CeF3, SmF3, NdF3, etc., and two or more may be used in combination.
[0023] The alkaline earth metal fluoride used to dope with lanthanide fluoride is not particularly limited as long as it has ionic conductivity, but examples include CaF2, SrF2, BaF2, etc., and two or more types may be used in combination.
[0024] Examples of lanthanides doped with alkaline earth metal fluorides include, for example, La 0.9 Ba 0.1 F 2.9 Ce 0.95 Ba 0.05 F 2.95 Ce 0.95 Sr 0.05 F 2.95 Ce 0.95 Ca 0.05 F 2.95 Examples include the following, and two or more may be used in combination.
[0025] The negative electrode active material may further contain a negative electrode active material other than a lanthanide fluoride that is doped with an alkaline earth metal fluoride.
[0026] Other than lanthanides doped with alkaline earth metal fluorides, the negative electrode active material is not particularly limited as long as it is a negative electrode active material used in fluoride ion secondary batteries.
[0027] (Conductive additive) The carbon material is not particularly limited as long as it has electronic conductivity, but it may be carbon black. Examples of carbon black include furnace black, Ketjen black, and acetylene black, and two or more types may be used in combination.
[0028] The conductive additive may further contain conductive additives other than carbon materials.
[0029] Other than carbon materials, the conductive additives are not particularly limited as long as they are conductive additives used in fluoride ion secondary batteries.
[0030] (Composite of lanthanide fluoride and carbon material) In a composite of lanthanide fluoride and carbon material, for example, at least a portion of the surface of the lanthanide fluoride particles is coated with the carbon material.
[0031] The particle size of the composite of lanthanide fluoride and carbon material is preferably 10 μm or less, and more preferably 5 μm or less. When the particle size of the composite of lanthanide fluoride and carbon material is 10 μm or less, the ionic conductivity and electronic conductivity are improved.
[0032] The mass ratio of the carbon material to the lanthanide fluoride doped with alkaline earth metal fluoride is preferably 3% by mass or more and 20% by mass or less, from the viewpoint of balancing ionic conductivity and electronic conductivity.
[0033] The content of the lanthanide fluoride-carbon material composite in the negative electrode layer is preferably 60% by mass or more and 70% by mass or less. When the content of the lanthanide fluoride-carbon material composite in the negative electrode layer is 60% by mass or more and 70% by mass or less, the discharge capacity of the fluoride ion secondary battery of this embodiment is improved.
[0034] (Method for producing composites of lanthanide fluoride and carbon materials) A method for producing a composite of lanthanide fluoride and a carbon material (hereinafter also referred to as the composite) includes a first step of obtaining a lanthanide fluoride-alkaline earth metal fluoride mixed powder, a second step of mixing the lanthanide fluoride-alkaline earth metal fluoride mixed powder with a carbon material to obtain a composite precursor, and a third step of calcining the composite precursor to obtain the composite.
[0035] The first step is to mix lanthanide fluoride and alkaline earth metal fluoride to obtain a lanthanide-alkaline earth metal fluoride mixed powder. In other words, by mixing lanthanide fluoride and alkaline earth metal fluoride, the solid-phase diffusion distance of elements derived from lanthanide fluoride and alkaline earth metal fluoride can be shortened during firing. Furthermore, a lanthanide-alkaline earth metal fluoride mixed powder is obtained in which the crystalline structures of lanthanide fluoride and alkaline earth metal fluoride do not remain after firing.
[0036] The method for mixing lanthanide fluorides and alkaline earth metal fluorides is not particularly limited, and either a dry method or a wet method may be used, but examples include mixing them using a mortar and pestle.
[0037] The temperature, time, and other conditions for mixing lanthanide fluorides and alkaline earth metal fluorides can be set as appropriate.
[0038] Furthermore, in the first step, the lanthanide fluoride-alkaline earth metal mixed powder may be pulverized.
[0039] Methods for grinding the lanthanide fluoride-alkaline earth metal mixed powder include, for example, grinding it using a ball mill.
[0040] The second step involves mixing the lanthanide fluoride-alkaline earth metal mixed powder obtained in the first step with a carbon material to obtain a composite precursor.
[0041] The method for producing the composite involves performing the second step prior to the third step, in which the carbon material is pre-mixed with the lanthanide fluoride-alkaline earth metal fluoride mixed powder. This yields a composite precursor in which the carbon material is arranged on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder.
[0042] Therefore, in the third step, by calcining the composite precursor, a composite is obtained in which at least a portion of the surface of the lanthanide fluoride particles doped with alkaline earth metal fluoride is coated with a carbon material.
[0043] Furthermore, in the second step, by placing a carbon material on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder, the grain growth of the lanthanide fluoride-alkaline earth metal fluoride mixed powder and the coarsening of the particle size due to fusion of particle interfaces are suppressed during the crystallization process in the third step, resulting in a composite in which the particle size of the lanthanide fluoride-alkaline earth metal fluoride mixed powder is maintained to approximately the same extent.
[0044] In the second step, the method for mixing the lanthanide fluoride-alkaline earth metal mixed powder with the carbon material is not particularly limited, and either a dry method or a wet method may be used, but examples include mixing using a mortar and pestle.
[0045] Furthermore, when mixing the lanthanide fluoride-alkaline earth metal mixed powder with the carbon material, it is preferable to apply shear force.
[0046] Furthermore, the temperature and other conditions for mixing the lanthanide fluoride-alkaline earth metal mixed powder with the carbon material can be set as appropriate.
[0047] Furthermore, in the second step, the composite precursor may be pulverized.
[0048] Methods for grinding the complex precursor include, for example, grinding it using a ball mill or grinding it using a mortar and pestle.
[0049] The third step involves calcining the composite precursor obtained in the second step to obtain the composite.
[0050] In the second step, a composite precursor is obtained in which a carbon material is arranged on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder. This suppresses grain growth and coarsening of the particle size due to fusion of particle interfaces in the lanthanide fluoride-alkaline earth metal fluoride mixed powder during the crystallization process in the third step, resulting in a composite obtained that maintains approximately the particle size of the composite precursor.
[0051] The conditions for calcining the composite precursor can be set as appropriate.
[0052] Furthermore, the composite material may be crushed in the third step.
[0053] Methods for grinding the composite include, for example, grinding it using a mortar and pestle.
[0054] (solid electrolyte) The solid electrolyte preferably contains nanoparticles of at least one of BaCaF4 and SrCaF4. This facilitates the securing of ion conduction paths and improves the discharge capacity of the fluoride-ion secondary battery in this embodiment.
[0055] The particle size of at least one of the BaCaF4 and SrCaF4 nanoparticles is, for example, between 30 nm and 200 nm.
[0056] The mass ratio of the total amount of BaCaF4 and SrCaF4 to cerium fluoride doped with alkaline earth metal fluoride is preferably 0.36 or more and 0.92 or less, from the viewpoint of balancing ionic conductivity and defluorination potential.
[0057] The solid electrolyte may further contain solid electrolytes other than BaCaF4 and SrCaF4.
[0058] The solid electrolyte other than BaCaF4 and SrCaF4 is not particularly limited, as long as it is a solid electrolyte used in fluoride ion secondary batteries.
[0059] [Positive electrode layer] The positive electrode layer contains a positive electrode active material and may further contain a conductive additive, a solid electrolyte, and the like.
[0060] (Cathode active material) The positive electrode active material contains a composite fluoride of copper and a fluorine compound. This improves the discharge capacity of the fluoride ion secondary battery. The fluorine compound is not particularly limited as long as it has ionic conductivity, but examples include lead fluoride (PbF2), tin fluoride (SnF2), bismuth fluoride (BiF3), lanthanum fluoride (LaF3), cerium fluoride (CeF3), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), etc. Two or more may be used in combination. Among these, sodium fluoride (NaF), potassium fluoride (KF), and barium fluoride (BaF2) are preferred.
[0061] The copper content in the composite fluoride of copper and fluorine compound is preferably 40 at% to 70 at%, and more preferably 50 at% to 60 at%. When the copper content in the composite fluoride of copper and fluorine compound is 40 at% to 70 at%, the discharge capacity of the fluoride ion secondary battery is improved.
[0062] The particle size of the copper-fluorine compound composite fluoride is preferably 100 nm or less, and more preferably 50 nm or less. When the particle size of the copper-fluorine compound composite fluoride is 50 nm or less, the diffusion distance of the fluoride ions is short, which improves the utilization rate of the positive electrode active material.
[0063] The content of the composite fluoride of copper and fluorine compound in the positive electrode layer is preferably 25% by mass or more and 70% by mass or less, and more preferably 50% by mass or more and 68% by mass or less, from the viewpoint of balancing ionic conductivity and electronic conductivity.
[0064] The positive electrode active material may further contain positive electrode active materials other than a composite fluoride of copper and a fluorine compound.
[0065] Aside from composite fluorides of copper and fluorine compounds, the positive electrode active material is not particularly limited as long as it is a negative electrode active material used in fluoride ion secondary batteries.
[0066] (Method for producing a composite fluoride of copper and fluorine compounds) A method for producing a composite fluoride of copper and a fluorine compound includes an aerosol process in which a molten raw material containing copper and a fluorine compound is sprayed under reduced pressure.
[0067] Specifically, first, copper and fluorine compounds are weighed and then mixed to obtain a raw material mixed powder. At this time, if necessary, the raw material mixed powder may be subjected to classification treatment. Next, the raw material mixed powder is melted using thermal plasma or the like to obtain a raw material molten material, and then the raw material molten material is sprayed into a chamber under reduced pressure. Next, the sprayed raw material molten material is cooled and formed into nanoparticles, and a composite fluoride of copper and fluorine compounds is obtained.
[0068] (Conductive additive) Examples of conductive additives include carbon materials.
[0069] The carbon material may be carbon black.
[0070] Examples of carbon black include furnace black, Ketjen black, and acetylene black, and two or more types may be used in combination.
[0071] (solid electrolyte) Examples of solid electrolytes include lanthanides doped with alkaline earth metal fluorides, BaCaF4, and PbSnF4. Among these, lanthanides doped with alkaline earth metal fluorides are preferred in terms of ionic conductivity and dielectric strength.
[0072] As the lanthanide fluoride doped with alkaline earth metal fluoride, compounds similar to the lanthanide fluoride doped with alkaline earth metal fluoride used as the negative electrode active material mentioned above can be used.
[0073] Furthermore, lanthanides doped with alkaline earth metal fluorides may be compounded with carbon materials, similar to the lanthanides doped with alkaline earth metal fluorides used as negative electrode active materials mentioned above.
[0074] In this case, it is preferable to wet-mix a composite fluoride of copper and a fluorine compound with a composite of lanthanide fluoride doped with alkaline earth metal fluoride and a carbon material, and then dry the mixture to produce the positive electrode layer. This suppresses aggregation of the composite fluoride of copper and a fluorine compound and the composite of lanthanide fluoride doped with alkaline earth metal fluoride and a carbon material, thereby improving the charge and discharge capacity of the fluoride ion secondary battery of this embodiment.
[0075] Examples of solvents used when wet-mixing a copper-fluorine compound composite fluoride with a carbon material composite of a lanthanide fluoride doped with an alkaline earth metal fluoride include cyclohexane and dimethyl carbonate.
[0076] The particle size of the composite of lanthanide fluoride and carbon material is preferably 10 μm or less, and more preferably 5 μm or less. When the particle size of the composite of lanthanide fluoride and carbon material is 10 μm or less, the ionic conductivity and electronic conductivity are improved.
[0077] The mass ratio of the carbon material to the lanthanide fluoride doped with alkaline earth metal fluoride is preferably 3% by mass or more and 20% by mass, from the viewpoint of balancing ionic conductivity and electronic conductivity.
[0078] [Solid electrolyte layer] The solid electrolyte layer contains BaCaF4. Therefore, the energy density of the fluoride-ion secondary battery in this embodiment is improved.
[0079] The solid electrolyte layer preferably contains BaCaF4 nanoparticles. This improves the energy density of the fluoride-ion secondary battery in this embodiment.
[0080] The particle size of at least one of the BaCaF4 and SrCaF4 nanoparticles is, for example, between 30 nm and 200 nm.
[0081] The solid electrolyte layer may further contain solid electrolytes other than BaCaF4.
[0082] The solid electrolyte other than BaCaF4 is not particularly limited, as long as it is a solid electrolyte used in fluoride ion secondary batteries.
[0083] [Positive electrode current collector and negative electrode current collector] Examples of positive electrode current collectors include gold foil. Similarly, examples of negative electrode current collectors include gold foil. [Examples]
[0084] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.
[0085] <Example 1> All-solid-state fluoride ion secondary batteries were fabricated using the following method. Unless otherwise specified, each step was performed inside a purge-type glove box DBO-1.5B (manufactured by Miwa Seisakusho) equipped with an argon gas circulation and purification system.
[0086] [Ce 0.95 Ba 0.05 F 2.95 - Fabrication of AB complex] (1st step) 8.598 g of CeF3 powder (manufactured by Sigma-Aldrich; 99.99% purity) and 0.402 g of BaF2 powder (manufactured by Kojun Chemical Laboratory; 99.9% purity) were weighed, and then mixed for 5 to 10 minutes using an agate mortar and pestle to obtain a CeF3-BaF2 mixed powder.
[0087] The CeF3-BaF2 mixed powder and 20 silicon nitride grinding balls (made by Fritsch) with a diameter of 10 mm were placed into a 80 cc silicon nitride ball mill pot, a dedicated container for the Premium Line PL-7 (made by Fritsch), and then sealed.
[0088] After removing the sealed ball mill pot from the glove box, the ball milling process was carried out. The grinding conditions were as follows:
[0089] Rotation speed: 800 rpm Grinding time: 60 minutes Number of crushing cycles: 40 Pause time between grinding processes: 5 minutes Rotation Reverse: ON
[0090] After the ball mill pot was brought into the glove box, the CeF3-BaF2 mixed powder was recovered from inside the ball mill pot.
[0091] (2nd process) Using an agate mortar and pestle, 3.08 g of CeF3-BaF2 mixed powder and 0.22 g of Denka Black (manufactured by Denki Kagaku Kogyo Co., Ltd.) as acetylene black (AB) were mixed, and Ce 0.95 Ba 0.05 F 2.95 -AB complex precursor obtained
[0092] Ce 0.95 Ba 0.05 F 2.95-AB composite precursor, 20 10mm diameter zirconia grinding balls (made by Fritsch), and 20 10mm diameter silicon nitride grinding balls (made by Fritsch) were placed into an 80cc silicon nitride ball mill pot, a dedicated container for the Premium Line PL-7 (made by Fritsch), and then sealed.
[0093] After removing the sealed ball mill pot from the glove box, the ball milling process was carried out. The grinding conditions were as follows:
[0094] Rotation speed: 800 rpm Grinding time: 60 minutes Number of crushing cycles: 40 Pause time between grinding processes: 5 minutes Rotation Reverse: ON
[0095] After bringing the ball mill pot into the glove box, Ce 0.95 Ba 0.05 F 2.95 -AB complex precursor was recovered. The recovered Ce 0.95 Ba 0.05 F 2.95 - The AB complex precursor was ground for 5-10 minutes using an agate mortar and pestle.
[0096] (3rd step) Ce 0.95 Ba 0.05 F 2.95 - The AB complex precursor was transferred to an alumina crucible, and then calcined using a small electric furnace KSL-1100X (manufactured by MTI) to Ce 0.95 Ba 0.05 F 2.95 -AB composite was obtained. The firing conditions were as follows:
[0097] Argon gas flow rate: 300cc / min Heating rate: 184℃ / h Maximum temperature reached: 1100℃ Holding time at the highest temperature reached: 1 hour Cooling rate: Uncontrolled Cooling method: natural cooling
[0098] From inside the alumina crucible, Ce 0.95 Ba 0.05 F 2.95 - After recovering the AB complex, it was ground for 5-10 minutes using an agate mortar and pestle.
[0099] [Preparation of BaCaF4] (Pre-mixing) After weighing 690 mg of barium fluoride powder (manufactured by Koshu Chemical Laboratory; 99% purity) and 310 mg of calcium fluoride powder (manufactured by Koshu Chemical Laboratory; 99.9% purity), the mixture was pre-mixed for approximately 1 hour using an agate mortar and pestle to obtain a BaF2-CaF2 mixed powder.
[0100] (Aerosol process) After the sealed powder hopper containing the BaF2-CaF2 mixed powder was removed from the glove box, it was connected to the TP-40020NPS high-frequency induction thermal plasma nanoparticle synthesis system (manufactured by JEOL).
[0101] Argon gas was supplied to a plasma torch, and the BaF2-CaF2 mixed powder was melted by thermal plasma to form a BaF2-CaF2 molten material. This BaF2-CaF2 molten material was then sprayed into a chamber under reduced pressure. The BaF2-CaF2 molten material sprayed into the chamber was cooled and broken down into nanoparticles, becoming BaCaF4. Next, the BaCaF4 was collected by an exhaust filter downstream of the apparatus. Then, the upstream and downstream sides of the exhaust filter were shut off with valves, and the BaCaF4 powder was transported into a glove box for recovery.
[0102] [Preparation of powder composition for negative electrode layer] Ce 0.95 Ba 0.05 F 2.95- 636 mg of AB complex, 4364 mg of BaCaF, and 40 g of 2 mm diameter silicon nitride grinding balls (made by Fritsch) were placed into a 45 cc silicon nitride ball mill pot, specifically designed for the Premium Line PL-7 (made by Fritsch), and then sealed.
[0103] After removing the sealed ball mill pot from the glove box, the ball milling process was carried out. The grinding conditions were as follows:
[0104] Rotation speed: 200 rpm Grinding time: 15 minutes Number of grinding processes: 10 Pause time between grinding processes: 5 minutes Rotation Reverse: ON
[0105] After the ball mill pot was brought into the glove box, the powder composition for the negative electrode layer was recovered from inside the ball mill pot.
[0106] [Preparation of Cu-BaF2 composite fluoride] (Pre-mixing) After weighing 480 mg of Cu metal powder (manufactured by Koshu Chemical Laboratory; purity 99.99%) with an average particle size of 1 μm and 190 mg of barium fluoride powder (manufactured by Koshu Chemical Laboratory; purity 99.9%), the mixture was pre-mixed for about 1 hour using an agate mortar and pestle to obtain a Cu-BaF2 mixed powder.
[0107] (Aerosol process) After the sealed powder hopper containing the Cu-BaF2 mixed powder was removed from the glove box, it was connected to the TP-40020NPS high-frequency induction thermal plasma nanoparticle synthesis system (manufactured by JEOL).
[0108] Argon gas was supplied to a plasma torch, and the Cu-BaF2 mixed powder was melted by the thermal plasma to form a Cu-BaF2 molten material. This Cu-BaF2 molten material was then sprayed into a chamber under reduced pressure. The Cu-BaF2 molten material sprayed into the chamber was cooled and broken down into nanoparticles, forming a Cu-BaF2 composite fluoride. Next, the Cu-BaF2 composite fluoride was collected by an exhaust filter downstream of the apparatus. Then, after the upstream and downstream sides of the exhaust filter were shut off with valves, the Cu-BaF2 composite fluoride was transported into a glove box and recovered.
[0109] [Preparation of powder composition for positive electrode layer] Cu-BaF2 complex fluoride 670 mg and Ce 0.95 Ba 0.05 F 2.95 - 330 mg of AB complex, 10 g of cyclohexane, and 40 g of 2 mm diameter silicon nitride grinding balls (made by Fritsch) were placed into a 45 cc silicon nitride ball mill pot, specifically designed for the Premium Line PL-7 (made by Fritsch), and then sealed.
[0110] After removing the sealed ball mill pot from the glove box, the ball milling process was carried out. The grinding conditions were as follows:
[0111] Rotation speed: 200 rpm Grinding time: 15 minutes Number of crushing cycles: 40 Pause time between grinding processes: 5 minutes Rotation Reverse: ON
[0112] After vacuum-drying the contents of the ball mill pot, the contents were transferred into a glove box and the powder composition for the cathode layer was recovered.
[0113] [Powder for solid electrolyte layer] BaCaF4, which was used in the preparation of the powder composition for the negative electrode layer, was used as the powder for the solid electrolyte layer.
[0114] [Fabrication of all-solid-state fluoride ion secondary batteries] Cylindrical pellet-type cells were manufactured by compacting powder using a tablet molder and pressing at a pressure of 40 MPa. Specifically, pellet-type cells were manufactured by feeding a 20 μm thick gold foil (manufactured by Niraco; purity 99.99%) as a negative electrode current collector, 30 mg of a powder composition for the negative electrode layer, 20 mg of powder for the solid electrolyte layer, 20 mg of powder composition for the positive electrode layer, and a 20 μm thick gold foil (manufactured by Niraco; purity 99.99%) as a positive electrode current collector into the tablet molder in this order.
[0115] <Comparative Example 1> An all-solid-state fluoride-ion secondary battery was prepared in the same manner as in Example 1, except that the powder for the negative electrode layer, the powder for the solid electrolyte layer, and the all-solid-state fluoride-ion secondary battery were prepared as follows.
[0116] [Preparation of powder for the negative electrode layer (PbSnF4-AB composite)] 63.7% by mass of lead fluoride powder (manufactured by High Purity Chemicals), 29.6% by mass of tin fluoride powder (manufactured by High Purity Chemicals), and 6.7% by mass of Denka Black (manufactured by Denka) as AB were mixed in a ball mill, and then calcined at 400°C for 1 hour under an argon atmosphere to obtain a PbSnF4-AB composite.
[0117] [Powder for solid electrolyte layer (Ce 0.95 Ba 0.05 F 2.95 [Production of] (1st step) 8.598 g of CeF3 powder (manufactured by Sigma-Aldrich; 99.99% purity) and 0.402 g of BaF2 powder (manufactured by Kojun Chemical Laboratory; 99.9% purity) were weighed, and then mixed for 5 to 10 minutes using an agate mortar and pestle to obtain a CeF3-BaF2 mixed powder.
[0118] The CeF3-BaF2 mixed powder and 20 silicon nitride grinding balls (made by Fritsch) with a diameter of 10 mm were placed into a 80 cc silicon nitride ball mill pot, a dedicated container for the Premium Line PL-7 (made by Fritsch), and then sealed.
[0119] After removing the sealed ball mill pot from the glove box, the ball milling process was carried out. The grinding conditions were as follows:
[0120] Rotation speed: 800 rpm Grinding time: 60 minutes Number of crushing cycles: 40 Pause time between grinding processes: 5 minutes Rotation Reverse: ON
[0121] After the ball mill pot was brought into the glove box, the CeF3-BaF2 mixed powder was recovered from inside the ball mill pot.
[0122] (2nd process) The CeF3-BaF2 mixed powder was transferred to an alumina crucible, and then calcined using a small electric furnace KSL-1100X (manufactured by MTI). 0.95 Ba 0.05 F 2.95 The result was obtained. The firing conditions at this time were as follows.
[0123] Argon gas flow rate: 300cc / min Heating rate: 184℃ / h Maximum temperature reached: 1100℃ Holding time at the highest temperature reached: 1 hour Cooling rate: Uncontrolled Cooling method: natural cooling
[0124] From inside the alumina crucible, Ce 0.95 Ba 0.05 F 2.95 After collection, the material was ground for 5-10 minutes using an agate mortar and pestle.
[0125] [Fabrication of all-solid-state fluoride ion secondary batteries] Cylindrical pellet-type cells were manufactured by compacting powder using a tablet molder and pressing at a pressure of 40 MPa. Specifically, pellet-type cells were produced by feeding the following into the tablet molder in this order: a 20 μm thick aluminum foil (manufactured by Niraco; purity 99+%) as the negative electrode current collector, 30 mg of powder for the negative electrode layer, 150 mg of powder for the solid electrolyte layer, 20 mg of powder composition for the positive electrode layer, and a 20 μm thick gold foil (manufactured by Niraco; purity 99.99%) as the positive electrode current collector.
[0126] [Particle size of powder] (Particle size of Cu-BaF2 composite fluoride and BaCaF4) The specific surface area of the powder was measured using a fully automatic specific surface area measuring device, Macsorb HM model-1208 (manufactured by Mountec). The particle size was then calculated from the specific surface area and true density of the powder.
[0127] As a result, the particle sizes of the Cu-BaF2 composite fluoride and BaCaF4 were 18 nm and 110 nm, respectively.
[0128] (Ce 0.95 Ba 0.05 F 2.95 -AB complex, Ce 0.95 Ba 0.05 F 2.95 (and particle size of the PbSnF4-AB composite) Using a scanning electron microscope SU-6600 (manufactured by Hitachi High-Technologies), the powder was imaged, and then the length of the powder in multiple SEM images was measured to determine the particle size.
[0129] As a result, Ce 0.95 Ba 0.05 F 2.95 -AB complex, Ce 0.95 Ba 0.05 F 2.95 The particle sizes of the PbSnF4-AB composite were 50 μm, 100 μm, and 100 μm, respectively.
[0130] [Charge / Discharge Test] Constant current charge-discharge tests were conducted on all-solid-state fluoride-ion secondary batteries. Specifically, using a potentiometer galvanostat SI1287 / 1255B (manufactured by Solartron), the tests were performed under vacuum and at 140°C, with a charge-discharge current of 0.04mA. In Example 1, the upper voltage limit was 3.8V and the lower voltage limit was 1.0V, while in Comparative Example 1, the upper voltage limit was 1.3V and the lower voltage limit was 0.3V. The tests were conducted starting with charging.
[0131] Figure 1 shows the initial charge-discharge curves of the all-solid-state fluoride-ion secondary batteries of Example 1 and Comparative Example 1.
[0132] Figure 1 shows that the all-solid-state fluoride-ion secondary battery of Example 1 has a higher charge / discharge capacity than the all-solid-state fluoride-ion secondary battery of Comparative Example 1.
[0133] Table 1 shows the evaluation results for discharge capacity, 50% discharge voltage, and energy density of the all-solid-state fluoride-ion secondary batteries of Example 1 and Comparative Example 1.
[0134] [Table 1]
[0135] Table 1 shows that the all-solid-state fluoride-ion secondary battery of Example 1 has higher charge / discharge capacity, 50% discharge voltage, and energy density than the all-solid-state fluoride-ion secondary battery of Comparative Example 1.
Claims
1. a positive electrode layer, a solid electrolyte layer, and a negative electrode layer; the positive electrode layer contains a positive electrode active material, the positive electrode active material contains a complex fluoride of copper and a fluorine compound, The solid electrolyte layer is BaCaF 4 Including, the negative electrode layer includes a negative electrode active material, a conductive additive, and a solid electrolyte, the negative electrode active material includes a lanthanide fluoride doped with an alkaline earth metal fluoride; the conductive additive contains a carbon material, The solid electrolyte contained in the negative electrode layer is BaCaF 4 and SrCaF 4 and The lanthanoid fluoride doped with the alkaline earth metal fluoride and the carbon material are composited together in the fluoride ion secondary battery.
2. The lanthanide fluoride is LaF 3 , CeF 3 , SmF 3 and NdF 3 2. The fluoride ion secondary battery according to claim 1, wherein the fluoride is one or more compounds selected from the group consisting of:
3. The alkaline earth metal fluoride is CaF 2 , SrF 2 and BaF 2 3. The fluoride ion secondary battery according to claim 1, wherein the fluoride is one or more compounds selected from the group consisting of:
4. The lanthanide fluoride doped with alkaline earth metal fluoride is La 0.9 Ba 0.1 F 2.9 , Ce 0.95 Ba 0.05 F 2.95 , Ce 0.95 Sr 0.05 F 2.95 and Ce 0.95 Ca 0.05 F 2.95 4. The fluoride ion secondary battery according to claim 1, wherein the fluoride is one or more compounds selected from the group consisting of:
5. The solid electrolyte contained in the negative electrode layer is BaCaF 4 and SrCaF 4 The fluoride ion secondary battery according to claim 1 , comprising nanoparticles of at least one of the above.
6. The solid electrolyte layer is BaCaF 4 6. The fluoride ion secondary battery according to claim 1, comprising nanoparticles of the formula: